2000
DOI: 10.1136/oem.57.10.678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of direction of rotation in continuous and discontinuous 8 hour shift systems

Abstract: Objectives-Previous research has produced conflicting evidence on the relative merits of advancing and delaying shift systems. The current study assessed the eVects of the direction of shift rotation within 8 hour systems, upon a range of measures including sleep, on shift alertness, physical health, and psychological wellbeing. Methods-An abridged version of the standard shiftwork index which included retrospective alertness ratings was completed by four groups of industrial shiftworkers on relatively rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
4
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 11 publications
4
52
4
4
Order By: Relevance
“…This was reflected in the increased fatigue ratings associated with quick returns (fatigue on the day following an on-call shift was not measured directly). These findings are concordant with previous research which suggests that quick returns are associated with restricted sleep (24), reduced alertness (25), and increased risk of accidents (26).…”
Section: Discussionsupporting
confidence: 83%
“…This was reflected in the increased fatigue ratings associated with quick returns (fatigue on the day following an on-call shift was not measured directly). These findings are concordant with previous research which suggests that quick returns are associated with restricted sleep (24), reduced alertness (25), and increased risk of accidents (26).…”
Section: Discussionsupporting
confidence: 83%
“…The results from this study conflict with the bulk of the literature regarding direction of shift rotation, but support more recent suggestions that there may be fewer differences in these kinds of schedules than was once thought (Tucker, Smith, Macdonald, & Folkard, 2000). They also support the theoretical work reported by Turek (1986) some years earlier that sleep patterns and circadian rhythms may be similarly affected by clockwise and counter-clockwise shift rotations.…”
Section: Discussioncontrasting
confidence: 56%
“…Instead, these results support more recent suggestions that there may be fewer differences in these kinds of schedules than was once thought (Tucker, Smith, Macdonald, & Folkard, 2000). In addition, the results agree with the findings from the first report in this series, which showed that rotation condition did not significantly affect sleep duration, sleep timing, or subjective reports of mood and fatigue.…”
Section: Discussionsupporting
confidence: 80%